Children Exploitation in Disruptive Technology Era: Child Endorsers in Indonesia - Suci Marini Novianty; Emma Rachmawati (Communicare : Journal of Communication Studies, 2019)
It is impossible to ignore the fact that social media as powerful marketing too in this disruptive era. The user, transform and claim themselves as a content creator, such as endorser and social media influencer. Meanwhile, children are also included in this social media endorser phenomenon. Children are juvenile and not capable of making decisions for themselves. This study aims to map how child exploitation in social media platforms, such as Instagram and YouTube, are conducted. Using the case study method, we observe various child influencer accounts. Based on the research, we found that there are several parties related to child exploitation in social media. Social-media platforms, advertisers, state agencies, followers or subscribers, parents, and children are the parties related to the case. Social-media platforms, verifying the underage accounts. Advertisers are those who choose the children endorser; State agencies as the lawmaker who let this kind of case slip without any further action; Follower or Subscriber who support the contents; Parents who play their power role to use their children; and children as the labor. These findings lead to conclude; children are regarded as workers who generate profit from investments made by their parents.